The Effect of Multiple Inteligence (MI) Towards The Character of Seventh Grade Students of IPA Madrasah Mu'allimin Muhammadiyah Yogyakarta - Azis, Taufik Burhanudin; Anwar, Syamsul; Bashori, Khoiruddin (Kaunia: Integration and Interconnection Islam and Science Journal, 2020)
The purpose of this research is to analyze the role of multiple intelligence toward solemn pray (sholat khusyuk) of seventh grade student of IPA of Madrasah Mu’alimin Muhammadiyah Yogyakarta. The research was done to contribute in theory development especially related to Islamic Psychology. It is expected to give the real contribution in increasing the solemn practice pray, especially in Madrasah Mu’alimin Muhammadiyah Yogyakarta. Eighty five students were used as sample in this research. The data were analyzed by multiple regression using SPSS program 19.00 version. The results of this research were: 1. The nine independent variables (linguistic intelligence, math logic, musical, kinesthetic, special-visual, interpersonal, intrapersonal, naturalistic, and existential) have roletoward dependent variable (solemn pray) and the  trend was positively significant. 2. The nine independent variables give contribution toward dependent variable 95,6%. 3. The independent variable that have dominant role is existencial variable namely 92,3% toward dependent variable. 4. The eight independent variable (linguistic intelligence, math logic, musical, kinesthetic, special-visual, interpersonal, intrapersonal, naturalistic) do not give significant contribution toward dependent variable.